Medicinal Orchids of Asia - Teoh, Eng Soon (Springer International Publishing : Imprint: Springer, 2016)
This unique book brings together a wealth of data on the botanical, ethno-medicinal and pharmacological aspects of over 500 species of Asian medicinal orchids. It starts off by explaining the role and limitations of complimentary and herbal medicines, and how traditional Asian medicine differs from Western, "scientific" medicine. The different Asian medical traditions are described, as well as their modes of preparing herbal remedies. The core of the book presents individual medicinal orchid species arranged by genera. Each species is identified by its official botanical name, synonyms, and local names. Its distribution, habitat and flowering season, uses and pharmacology are described. An overview sums up the research findings on all species within each genus. Clinical observations are discussed whenever available, and possible therapeutic applications are highlighted. The book closes with chapters on the conservation of medicinal orchids and on the role of randomized clinical trials.